Is health-related quality of life of patients after single-use flexible ureteroscopy superior to extracorporeal shock wave lithotripsy? A randomised prospective study - Svihra, Jan; Sopilko, Igor; Svihrova, Viera; Student, Vladimir; Luptak, Jan (Urolithiasis, 2021)
The aims of the study were to compare the change in the Wisconsin Stone Quality of Life (WISQOL) score in patients who underwent retrograde intrarenal surgery (RIRS) single-use ureteroscope or extracorporeal shock wave lithotripsy (ESWL) with a calculation of quality-adjusted life-years (QALYs). 158 patients treated with urinary stone disease were randomly divided into 80 patients in the validation and 78 patients in the intervention arm. Patients in the intervention arm were randomly divided into the RIRS or the ESWL group. Linguistic validation of the WISQOL into the Slovak language was performed using a standardised multistep process. Discriminant validity was assessed by comparing stone-forming patients to an additional 34 healthy individuals. Patients were asked to fill in the WISQOL before and in the 24th week after the intervention. The QALYs were calculated by the formula QALY = weight factor (WF) x time period after intervention. The Cronbach's α of the WISQOL was 0.94, the Pearson's coefficient for test-retest reliability was 0.91, and the discriminant validity confirmed a higher score for healthy individuals (p < 0.001). The median WISQOL score changed from 45.5 to 95.5 vs. 33.9 to 87.1 in the RIRS and ESWL groups, respectively (p < 0.001). Patients from the RIRS group had a good possibility of reaching 19.727 QALYs gained during life expectancy compared to 15.780 for the ESWL group (p < 0.001). RIRS single-use ureteroscope is significantly superior to ESWL in reaching more QALYs gained during life expectancy. The WISQOL Slovak version is valid, reliable and strictly specific for stone-forming patients.
Keywords: Ureteroscopes; překládání; Surveys and Questionnaires; Humans; lidé středního věku; litotripse; RIRS; Quality of Life; Lithotripsy; ureteroskopie; Female; Aged; Translating; HRQOL; výsledek terapie; senioři; lidé; ureteroskopy; kvalita života; reprodukovatelnost výsledků; Urinary Calculi; průzkumy a dotazníky; Quality-Adjusted Life Years; močové kameny; Ureteroscopy; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Psychometrics; Treatment Outcome; kvalitativně upravené roky života; ESWL; mužské pohlaví; prospektivní studie; Urinary stone disease; psychometrie; Prospective Studies